HIV and hepatitis B, C co-infection and correlates of HIV infection among men who have sex with men in Rwanda, 2021: a respondent-driven sampling, cross-sectional study - Eric Remera; Elysee Tuyishime; Catherine Kayitesi; Samuel S. Malamba; Beata Sangwayire; Justine Umutesi; Horacio Ruisenor-Escudero; Tom Oluoch (BMC Infectious Diseases, 2024)
Abstract Background Men who have sex with men (MSM) are a key population group disproportionately affected by HIV and other sexually transmitted infections (STIs) worldwide. In Rwanda, the HIV epidemic remains a significant public health concern, and understanding the burden of HIV and hepatitis B and C coinfections among MSM is crucial for designing effective prevention and control strategies. This study aims to determine the prevalence of HIV, hepatitis B, and hepatitis C infections among MSM in Rwanda and identify correlates associated with HIV infection within this population. Methods We used respondent-driven sampling (RDS) to recruit participants between November and December 2021. A face-to-face, structured questionnaire was administered. Testing for HIV infection followed the national algorithm using two rapid tests: Alere Combo and STAT PAK as the first and second screening tests, respectively. Hepatitis B surface antigen (HBsAg) and anti-HCV tests were performed. All statistics were adjusted for RDS design, and a multivariable logistic regression model was constructed to identify factors associated with HIV infection. Results The prevalence of HIV among MSM was 6·9% (95% CI: 5·5–8·6), and among HIV-positive MSM, 12·9% (95% CI: 5·5–27·3) were recently infected. The prevalence of hepatitis B and C was 4·2% (95% CI: 3·0–5·7) and 0·7% (95% CI: 0·4–1·2), respectively. HIV and hepatitis B virus coinfection was 0·5% (95% CI: 0·2–1·1), whereas HIV and hepatitis C coinfection was 0·1% (95% CI: 0·0–0·5), and no coinfection for all three viruses was observed. MSM groups with an increased risk of HIV infection included those who ever suffered violence or abuse because of having sex with other men (AOR: 3·42; 95% CI: 1·87–6·25), those who refused to answer the question asking about ‘ever been paid money, goods, or services for sex’ (AOR: 10·4; 95% CI: 3·30–32·84), and those not consistently using condoms (AOR: 3·15; 95% CI: 1·31–7·60). Conclusion The findings suggest more targeted prevention and treatment approaches and underscore the importance of addressing structural and behavioral factors contributing to HIV vulnerability, setting interventions to reduce violence and abuse against MSM, promoting safe and consensual sexual practices, and expanding access to HIV prevention tools such as condoms and preexposure prophylaxis (PrEP).